Upaya Peningkatan Kemampuan Membaca Puisi dengan Metode Cooperative Script pada Peserta Didik Kelas XI SMA Muhammadiyah Kupang - Siti Susanti Mallida Djaha; Ahmad Ahmad (STKIP PGRI SITUBONDO, 2022)
This study aims to describe the process of learning to read poetry with the cooperative script method and describe the results of learning to read poetry using the cooperative script method for class XI students of Senior High School Muhammadiyah Kupang in the 2020/2021 school year. This type of research is Classroom Action Research. Data collection techniques are observation, test and documentation. The data analysis technique used are descriptive qualitative and quantitative analysis techniques. Qualitative analysis techniques to obtain student responses to learning activities. Quantitative analysis techniques used to describe the data from the results of students' ability to read poetry and take tests at the end of each cycle. The results showed that the results of the poetry reading skills test with the cooperative script method carried out in both cycles showed that the students experienced an increase in grades of 49.5%, the average value of students from 64.66 in the first cycle increased to the average score 76.54 in the second cycle. It is proven that students have increased in every aspect of reading poetry in the first cycle and the second cycle. Therefore, the cooperative script method can improve students' ability to read poetry in class XI students of Senior High School Muhammadiyah Kupang for the 2020/2021 school year.